Corporate governance structure, firm characteristics and voluntary disclosure: The case of Indonesian sharia compliant companies - Nugraheni, Peni; Muhammad Eko, Rahardianto; Aziz, Nor Izzati Mohd (Jurnal Akuntansi dan Auditing Indonesia, 2024)
The study aims to examine the influence of corporate governance structure that includes ownership structure, board of directors’ size, board of commissioner’s size, and audit firm type to the Islamic voluntary disclosure (IVD) in the Indonesian sharia-compliant companies listed on Jakarta Islamic Index 70 (JII70). Voluntary disclosure in this study is measured using the Islamic disclosure index. This study analyses the data using multiple regression. The results show that the board of directors’ size significantly positively affects Islamic voluntary disclosure, while the ownership structure, type of audit firm and board of commissioners' size do not significantly affect the extent of Islamic voluntary disclosure. These results imply that voluntary disclosure is very dependent on the will of internal parties. The board of directors can encourage wider disclosure, especially in sharia aspects, thereby further emphasizing its status as a sharia compliance company.